MEMBANGUN MODEL PENDIDIKAN KEHIDUPAN BERAGAMA BERBASIS LIFE SKILLS DI PESANTREN: Studi Kasus di SMK Roudlotul Mubtadiin Jepara dan Madrasah Aliyah Al Hikmah 2 Brebes - Mudzakkir Ali (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2012)
AbstractThe research objective is to build an education model of religious life based on life skills in the Islamic boarding school according to the philosophy of life of the nation. This study used Borg and Gall development procedure consisting of three stages of development, namely pre-development, development and post-development. Activities undertaken in the pre-development stage is to conduct literary study. The development stage includes the steps of drafting a guidance to formulate general objective, special objective, developing evaluation tools and determining strategy. The post-development stage includes expert test, small group test and limited group test. The expert assessment results show that education model of the religious life based on life skills in Islamic boarding school have met the acceptability criteria when viewed from the usability, feasibility and accuracy aspects. The study results are in two schools in the Islamic boarding school surrounding, namely Islamic Senior High School (MA) Al Hikmah 2 and Vocational School (SMK) Roudlotul Mubtadiin, which have organized life skills education although with different variants, i.e. materials of vocational education programs in the extra-curricular activitiÂes, such as: computer, English, fashion, fisheries, electronics, automotive, welding, and Kitab Kuning (Islamic books). The implementation of life skills education is not limited to the level of regulatory structure, both in the curriculum and in the educational process, but also the effectiveness of education contained in the culture system of religious life in developing life skills in the Islamic boarding school environment.AbstrakTujuan penelitian ini untuk membangun model pendidikan kehidupan beragama berbasis life skills di pesantren sesuai dengan falsafah hidup bangsa. Penelitian ini menggunakan prosedur pengembangan Borg and Gall yang terdiri atas tiga tahapan pengembangan, yaitu pra pengembangan, pengembangan dan pasca pengembangan. Kegiatan yang dilakukan pada tahap pra pengembangan adalah melakuÂkan telaah literatur. Tahap pengembangan meliputi langkah-langkah menyusun draf panduan dengan merumuskan tujuan umum, tujuan khusus, mengembangkan alat evaluasi dan menentukan strategi. Tahap pasca pengembangan yaitu melakukan uji ahli, uji kelompok kecil dan uji kelompok terbatas. Hasil penilaian ahli menunjukkan bahwa model pendidikan kehidupan beragama berbasis life skills di pesantren telah memenuhi kriteria akseptabilitas bila ditinjau dari aspek kegunaan, kelayakan dan ketepatan. Hasil penelitian adalah pada dua sekolah di lingkungan pesantren yaitu MA Al Hikmah 2 dan SMK Roudlotul Mubtadiin, telah menyelenggarakan pendidikan life skills walaupun dengan varian yang berbeda, yaitu materi program pendidikan keterampilan dalam kurikulum ekstra kurikuler, seperti: komputer, bahasa Inggris, tata busana, perikanan, elektronika, otomotif, pengelasan, dan kitab turats. Implementasi pendidikan life skills tidak sebatas pada tataran struktur regulatif, baik dalam muatan kurikulum maupun proses pendidikannya, tetapi efektivitas pendidikan terdapat pada sistem kultur kehidupan beragama dalam mengembangkan life skills di dalam lingkungan pesantren.